Integrated Health Post for Child Health (Posyandu) As A Community-Based Program in Indonesia: An Exploratory Study - Agus Setiawan; Yodi Christiani (Jurnal Keperawatan Indonesia, 2018)
Integrated Health Post for Child Health (Posyandu) has been endorsed since 1984 as a community-based health program in Indonesia. Despite its potential in improving child health outcomes, evidence related to its current implementation is lacking. This study aimed to explore the current implementation of posyandu in the country. Data of 638 posyandu surveyed in the 5th wave of Indonesia Family Life Survey (IFLS-5) located in urban and rural areas were analyzed, applying chi-square and independent t-test method. Posyandu surveyed run a number of activities (mean type of activities=8.1 in rural vs. 7.4 in urban areas, p<0.001), focusing on weight monitoring, supplementary food provision, and vitamin A supplementation. Approximately 38% of Community Health Workers (CHWs) has never been trained in posyandu’s management nor child health care. Financial barriers, medicine and equipment supplies, and location to conduct posyandu’s activities remained as challenges in the implementation. While posyandu has been implemented for decades, the study found that its implementation has not been optimal. Actions should be taken to improve posyandu’s implementation. These include strengthening collaboration to address the problems and improving CHWs activities.  Keywords: posyandu, child health, community-based health program